2023
DOI: 10.1101/2023.03.10.23286921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histological examination of choroid plexus epithelia changes in schizophrenia

Abstract: Background. The choroid plexus (CP) is suggested to be involved in neuroimmune regulation avia the interaction between central and peripheral inflammation. Quantitative imaging has demonstrated volumetric CP change in psychosis, schizophrenia and depression. This study histologically examines CP epithelial cell morphology in these illnesses to identify the biological source of such volumetric changes. Methods. Formalin-fixed paraffin-embedded FFPE blocks were obtained bilaterally from the lateral ventricles of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…In line with those findings, increased ChP volumes, altered ChP epithelia, and associated upregulation of immune genes in the ChP were described in individuals with SSD 1416 . Located in each brain ventricle, the ChP produces CSF and forms the BCB, thus regulating central nervous system (CNS) homeostasis 17 .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with those findings, increased ChP volumes, altered ChP epithelia, and associated upregulation of immune genes in the ChP were described in individuals with SSD 1416 . Located in each brain ventricle, the ChP produces CSF and forms the BCB, thus regulating central nervous system (CNS) homeostasis 17 .…”
Section: Introductionsupporting
confidence: 82%
“…Even though we showed a moderate correlation between FreeSurfer segmentation and manual segmentation of ChP, some authors have questioned the reliability of FreeSurfer segmentation of ChP and have suggested other more reliable methods 43, 59 . Furthermore, since only nine of the individuals with SSD in our cohort were antipsychotic-naïve, we cannot exclude medication effects on choroid plexus morphology 21 . The individual clusters (especially cluster 1) might have been underpowered to detect differences regarding clinical and immunological features.…”
Section: Discussionmentioning
confidence: 99%